From single to multiple assessments in a foundational mathematics course for engineering students: what do we gain? - Zakariya, Yusuf Feyisara; Berg, Morten Tellenes; Gjesteland, Thomas; Umahaba, Ramatu Ematum; Abanikannda, Mukhtar Oluwafemi (Frontiers in Education, 2025)
BackgroundIn response to high failure rates in foundational mathematics courses, the traditional single high-stakes final examination was replaced with four digital tests, with multiple attempts, and a hand-in project.ObjectivesThis study evaluates the impact of this reformed assessment strategy on a first-year calculus course for engineering students at a Norwegian university. We explored students' perceptions of the reformed assessment regarding their learning approaches, motivation, and the overall experience.MethodsWe generated the data using semi-structured interviews of purposively selected engineering students and analyzed the data using thematic analysis.ResultsThe results showed that the multiple attempts on the examinations promoted consistent studying and reduced test anxiety. Additionally, students reported positive experience with collaborative learning, enhanced by peer learning and diverse perspectives during group work. Although students appreciated the flexibility of digital examinations, they noted limitations in feedback on minor errors.ConclusionThis research highlights the effectiveness of multiple low-stakes assessments in enhancing a supportive learning environment and suggests that digital tools can improve engagement and understanding in mathematics. The findings have implications for rethinking assessment practices in STEM education and offer insights into how digital assessments can mitigate the challenges students face in foundational courses.